Seven Days In Nicaragua Libre - Ferlinghetti, Lawrence (City Lights Books, San Francisco, 1984)
I went to Nicaragua in the last week of January, 1984, to give the poet and minister of culture, father Ernesto Cardenal, a seed from a flower at boris Pasternaks grave which han been given to me by the Russian poet Andrei voznesenski at a poetry reading against war at UNESCO in Paris.